Language as a Vehicle in The Quest for Identity in Chinua Achebe's Things Fall Apart - Missaoui, Sara; Aribi, Brahim (Faculty of Letters and Foreign Languages Department of English, 2018)
The issues of language and identity are very prominent themes in postcolonial literature. The exploration of the postcolonial writers as Chinua Achebe in terms of the depiction of their cultural identities and of their people’s reveals the culture of the postcolonial writers. These writers tackle the influence of decolonization, language, and identity. Their attempt is to reconstruct identity or to reinvent a new one. In the discussion of the works of Chinua with his personal views on an identity question we will see how he views this subject matter as a postcolonial writer and from a personal perspective, and also through his novel Things Fall Apart. Moreover, language is a fundamental characteristic of every human society. The language one speaks tells much about one’s identity with regards to where the person comes from. In every society, individuals and groups of persons would like to be differentiated from others, and in that effect, identity comes to play. So, this study highlights the topic of post colonialism and its relation with language and identity, and it also discusses the issues regarding the use of language as a means of quest for identity in Things Fall Apart. However, at the end of the research, it is discovered that Achebe has been able to use language as a quest for identity in his novel